Case report: Episodic ataxia without ataxia? - Gaudio, Andrea; Gotta, Fabio; Ponti, Clarissa; Sanguineri, Francesca; Trevisan, Lucia; Geroldi, Alessandro; Patrone, Serena; Gemelli, Chiara; Cabona, Corrado; Astrea, Guja; Fiorillo, Chiara; Gustincich, Stefano; et al. (Frontiers in Neurology, 2023)
Hereditary myopathies represent a clinically and genetically heterogeneous group of neuromuscular disorders, characterized by highly variable clinical presentations and frequently overlapping phenotypes with other neuromuscular disorders, likely influenced by genetic and environmental modifiers. Genetic testing is often challenging due to ambiguous clinical diagnosis. Here, we present the case of a family with clinical and Electromyography (EMG) features resembling a myotonia-like disorder in which Whole Exome Sequencing (WES) analysis revealed the co-segregation of two rare missense variants in UBR4 and HSPG2, genes previously associated with episodic ataxia 8 (EA8). A review of the literature highlighted a striking overlap between the clinical and the molecular features of our family and the previously described episodic ataxias (EAs), which raises concerns about the genotype–phenotype correlation, clinical variability, and the confounding overlap in these groups of disorders. This emphasizes the importance of thoroughly framing the patient's phenotype. The more clear-cut the diagnosis, the easier the identification of a genetic determinant, and the better the prognosis and the treatment of patients.